Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex]\int 3^{\tfrac{x}{2}}\, dx=(*)\\
t=\dfrac{x}{2}\\
dt=\dfrac{x}{2}\, dx\\
dx=2\, dt\\
(*)=\int 3^t\cdot2\, dt=\\
2\int 3^t \, dt=\\
2\cdot\dfrac{3^t}{\ln 3}+C=\\
\boxed{\dfrac{2\cdot3^{\tfrac{x}{2}}}{\ln 3}+C}
[/tex]
[tex]\int { { 3 }^{ \frac { x }{ 2 } } } dx\\ \\ =\int { { \left( { 3 }^{ x } \right) }^{ \frac { 1 }{ 2 } } } dx[/tex]
However:
[tex]u={ 3 }^{ x }\\ \\ \therefore \quad \frac { du }{ dx } ={ 3 }^{ x }\cdot \ln { 3 } \\ \\ \therefore \quad du={ 3 }^{ x }\cdot \ln { 3 } dx\\ \\ \therefore \quad dx=\frac { 1 }{ { 3 }^{ x }\cdot \ln { 3 } } du=\frac { 1 }{ u\cdot \ln { 3 } } du[/tex]
So let's use:
[tex]\int { { u }^{ \frac { 1 }{ 2 } } } \cdot \frac { 1 }{ u\cdot \ln { 3 } } du\\ \\ =\int { \frac { 1 }{ \ln { 3 } } } \cdot { u }^{ -\frac { 1 }{ 2 } }du[/tex]
But you need to know that:
[tex]\int { k{ u }^{ n } } du\\ \\ =\frac { k{ u }^{ n+1 } }{ n+1 } +C[/tex]
Therefore:
[tex]\int { \frac { 1 }{ \ln { 3 } } } \cdot { u }^{ -\frac { 1 }{ 2 } }du\\ \\ =\frac { \frac { 1 }{ \ln { 3 } } \cdot { u }^{ \frac { 1 }{ 2 } } }{ \frac { 1 }{ 2 } } +C[/tex]
[tex]\\ \\ =\frac { 1 }{ \ln { 3 } } \cdot { u }^{ \frac { 1 }{ 2 } }\cdot 2+C\\ \\ =\frac { 1 }{ \ln { 3 } } \cdot { 3 }^{ \frac { x }{ 2 } }\cdot 2+C\\ \\ =\frac { 2\cdot { 3 }^{ \frac { x }{ 2 } } }{ \ln { 3 } } +C[/tex]
However:
[tex]u={ 3 }^{ x }\\ \\ \therefore \quad \frac { du }{ dx } ={ 3 }^{ x }\cdot \ln { 3 } \\ \\ \therefore \quad du={ 3 }^{ x }\cdot \ln { 3 } dx\\ \\ \therefore \quad dx=\frac { 1 }{ { 3 }^{ x }\cdot \ln { 3 } } du=\frac { 1 }{ u\cdot \ln { 3 } } du[/tex]
So let's use:
[tex]\int { { u }^{ \frac { 1 }{ 2 } } } \cdot \frac { 1 }{ u\cdot \ln { 3 } } du\\ \\ =\int { \frac { 1 }{ \ln { 3 } } } \cdot { u }^{ -\frac { 1 }{ 2 } }du[/tex]
But you need to know that:
[tex]\int { k{ u }^{ n } } du\\ \\ =\frac { k{ u }^{ n+1 } }{ n+1 } +C[/tex]
Therefore:
[tex]\int { \frac { 1 }{ \ln { 3 } } } \cdot { u }^{ -\frac { 1 }{ 2 } }du\\ \\ =\frac { \frac { 1 }{ \ln { 3 } } \cdot { u }^{ \frac { 1 }{ 2 } } }{ \frac { 1 }{ 2 } } +C[/tex]
[tex]\\ \\ =\frac { 1 }{ \ln { 3 } } \cdot { u }^{ \frac { 1 }{ 2 } }\cdot 2+C\\ \\ =\frac { 1 }{ \ln { 3 } } \cdot { 3 }^{ \frac { x }{ 2 } }\cdot 2+C\\ \\ =\frac { 2\cdot { 3 }^{ \frac { x }{ 2 } } }{ \ln { 3 } } +C[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.